2020
DOI: 10.1016/j.healthpol.2019.12.004
|View full text |Cite
|
Sign up to set email alerts
|

The development of the Primary Care Clusters Multidimensional Assessment (PCCMA): A mixed-methods study

Abstract: A strong primary care (PC) system is essential for an efficient and high-quality healthcare service. Many countries have adopted a model of PC that encourages different healthcare providers to work together, at scale, in multidisciplinary/multiagency teams (PC clusters). The aim of the present work was to develop a quantitative instrument for the systematic and comprehensive assessment of PC clusters. This was a non-experimental, mixed-methods study grouping four work packages (WP), and involving PC cluster le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(25 citation statements)
references
References 19 publications
(27 reference statements)
0
22
0
Order By: Relevance
“…Similar to findings from a study involving Welsh cluster leads, 28 some participants were also uncertain about how clusters will evolve. Uncertainty for these Welsh leads related to future funding arrangements for their clusters, but the participants in this study were concerned more with tensions around expectation for CQLs to ‘police’ or collaboratively engage with their cluster members.…”
Section: Discussionmentioning
confidence: 55%
See 2 more Smart Citations
“…Similar to findings from a study involving Welsh cluster leads, 28 some participants were also uncertain about how clusters will evolve. Uncertainty for these Welsh leads related to future funding arrangements for their clusters, but the participants in this study were concerned more with tensions around expectation for CQLs to ‘police’ or collaboratively engage with their cluster members.…”
Section: Discussionmentioning
confidence: 55%
“… 29 The internally driven collaboration observed in this study is arguably a firm foundation on which clusters can improve their integration with local public health and social care agencies, structures, and processes. 28 , 30…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Representativeness was examined by comparison with national GP data. 16 The survey was broadly representative in terms of gender, age, rurality, and deprivation (Supplementary Table 1).…”
Section: Participants and Representativenessmentioning
confidence: 99%
“…A recent study from Wales reported on the development of a primary care clusters multidimensional assessment (PCCMA) which had been piloted on 38 CQLs, consisting of 53 indicators across 11 systemic dimensions of primary care. 16 Reliability and validity analysis was absent, presumably due to the small sample size. It is noteworthy that the bespoke items in the current study overlap with items and concepts in nine of the 11 PCCMA dimensions.…”
Section: Comparison With Existing Literaturementioning
confidence: 99%